A KPP road–field system with spatially periodic exchange terms. (November 2015) - Giletti, Thomas; Monsaingeon, Léonard; Zhou, Maolin
Abstract: We take interest in a reaction–diffusion system which has been recently proposed (Berestycki and Roquejoffre, 2013) as a model for the effect of a road on propagation phenomena arising in epidemiology and ecology. This system consists in coupling a classical Fisher–KPP equation in a half-plane with a line with fast diffusion accounting for a straight road. The effect of the line on spreading properties of solutions (with compactly supported initial data) was investigated in a series of works starting from Berestycki and Roquejoffre (2013). We recover these earlier results in a more general spatially periodic framework by exhibiting a threshold for road diffusion above which the propagation is driven by the road and the global speed is accelerated. We also discuss further applications of our approach, which will rely on the construction of a suitable generalized principal eigenvalue, and investigate in particular the spreading of solutions with exponentially decaying initial data.